Chapter The Value Proposition of Organizations for Young Graduates and their Employability - Torlone, Francesca (Studies on Adult Learning and Education, 2018)
Certain young people are being propelled towards a more promising future than in the past, due to - amongst other things - continuous learning, which guarantees their productive capabilities. Employers are called upon to arrange a cogent value proposition to support young people in their constant growth that would also help them create an autonomous professional identity